Ultrasound-Guided Central Vein Catheterization in Pediatrics - M. A. Leontiev; S. V. Kravchuk; A. V. Vodova (Неотложная медицинская помощь)
ABSTRACT In this article the most relevant methods of subclavian vein catheterization were considered in order to find the optimal technique that can be used in routine clinical practice by pediatric intensive care physicians.OBJECTIVE To compare the efficiency and safety of subclavian vein catheterization by supraclavicular access under ultrasound control and subclavian access by anatomical landmarks in children.RESULTS The number of attempts for successful catheterization was statistically lower in ultrasound-control group compared to the anatomical landmarks group (1.2±0.4 vs. 2.6±1.3, p<0.0001); in the anatomical landmarks group such complications as catheter malposition (14% vs. 0), arterial puncture (5% vs. 1%) and pneumothorax (10% vs. 0) were observed more often than in the ultrasound group.CONCLUSIONS We recommend catheterization of the subclavian vein by supraclavicular access under ultrasound control to be commonly used in clinical practice due to its high efficiency and safety.